Factors Influencing the Willingness to Adopt Internet of Things in Supply Chain Management: A Study on Bangladeshi Manufacturing Firms - Islam, Saiful (Dhaka University Journal of Business Studies, 2026)
This study explores the factors influencing the willingness to adopt the Internet of Things (IoT) in Bangladeshi manufacturing firms' supply chain management (SCM). Using a quantitative research approach, data is collected from 162 firm-specific SCM professionals through purposive sampling. Applying the partial least squares structural equation modeling (PLS-SEM), the four primary constructs of the Unified Theory of Acceptance and Use of Technology (UTAUT) model- performance expectancy, effort expectancy, social influence, and facilitating conditions are examined to find their influence on the willingness to adopt IoT in the SCM of Bangladeshi manufacturing firms. Findings enumerate that these four constructs explain 42% of the variance in the willingness to adopt IoT. Performance expectancy, social influence, and facilitating conditions are statistically significant, while effort expectancy is insignificant in influencing the willingness to adopt IoT in the SCM. These findings bring several theoretical and practical contributions and suggest scope for future research. Journal of Business Studies, Vol. XLIV, No. 1, 2025 Page 77-105